Penerapan Konsep Limit Fungsi dalam Kehidupan - Riesa Riskania Yuniman; Fikri Bakti Ridayana; Kristina Siagian; Dinda Nurfadilah; Ahmad Fu’adin (Lembaga Pengembangan Kinerja Dosen, 2022)
Limit of a function is the main of calculus that teached in high school. The concept is the value of a function gets closer or approaches some number. This research focuses on finding the use of the limit function concept in every sectors in our daily, inside and outside the mathematic. This research was conducted to increase motivation to students in studying limit of functions in school and to become a source of knowledge for others. The research method used is study literature. The result of this reseach is the concept of limit function widely used in various sectors of life. In engineering, the concept of limit is used to calculate the speed and maximum output of a machine. In science, the concept of limit exists in mathematics, physics, and chemistry. In the health sector, the concept of limit is used in the eye checkup and in daily, the concept of limit is used with the expression almost, that something is only close, but does not happen.